Sport Tourism Event of Tour De Singkarak to Support Destination Management in West Sumatera, Indonesia - Silisna, Bet El; Susanti, Retnaningtyas (E-Journal of Tourism, 2020)
This study aims to analyze the sport tourism event of Tour de Singkarak (TdS) related to tourist destination management in West Sumatera, Indonesia. The TdS is an international road bicycle race held annually for ten-year period as data presented from 2009 to 2018. Data were collected for this study through in-depth interviews with informants and analyzed by a descriptive qualitative technique. The results showed that the TdS events were succesfully and consistently held annually for ten-year period of 2009-2018 in West Sumatera and has significantly contributed to the regionas tourism destination. This was due to a strong commitment and serious action among central government and local government at province and municipality levels for the sport tourism development at the tourism destination in West Sumatera. The commitment could be seen in the serious, strong commitment and coordination between the Ministry of Tourism and the National Road Development Agency at a central government and Heads of Local Departments of Tourism, of Public Works and of Transportation at province and regency/municipality level. The commitment could be seen from the sport tourism management such as the provision of shared budget, event coordination, and destination and infrastructure development and promotion. This has especially raised an integrated development and improvement of infrastructures, i.e. roads, transportation mode, and accomodation facilities with increasing quantity and quality. It is a fact that TdS could be held annually for ten-year period (2009-2018) along with proper and good destination management for sport tourism in West Sumatera Province. Keywords: Tour de Singkarak, event, sport tourism, destination management.